Significance of Epidermal Growth Factor Receptor (EGFR) upregulation in the prediction of the malignant transformation risk in oral potentially malignant disorders: a systematic review and meta-analysis - Cívico-Ortega, José Luis; Ramos-García, Pablo; González-Moles, Miguel Ángel (Frontiers in Oral Health, 2025)
ObjectivesThe purpose of this systematic review and meta-analysis was to appraise, both quantitatively and qualitatively, the extant evidence regarding the role of EGFR upregulation in predicting malignant transformation risk associated with oral potentially malignant disorders (OPMD).MethodsA comprehensive search was undertaken in the Web of Science, Embase, MEDLINE (via PubMed), and Scopus databases for longitudinal primary-level articles, whether prospective or retrospective in design, without restrictions on language or publication date. The QUIPS tool was employed for the purpose of assessing the potential for bias. A meta-analysis was conducted in addition to sensitivity analyses and analyses of the potential influence of small-study effects.ResultsIn total, eight studies, which were treated as nine distinct units for analytical purposes, were included in the final sample, which encompassed 653 patients with OPMD with follow-up data. EGFR upregulation was found to be significantly associated with an elevated malignant transformation risk of OPMD (RR = 2.17, 95%CI = 1.73–2.73, p < 0.001). Subgroup analyses demonstrated that both EGFR protein overexpression (RR = 2.02, 95%CI = 1.55–2.63, p < 0.001) and EGFR gene amplification (RR = 2.70, 95%CI = 1.72–4.25, p < 0.001), nuclear staining (RR = 3.47, 95%CI = 1.50-8.01, p = 0.004) and the >10% cutoff point were significantly associated with transformation risk (RR = 2.27, 95%CI = 1.33–3.87, p = 0.003).ConclusionThe present systematic review and meta-analysis demonstrates that EGFR overexpression, assessed through immunohistochemical technique, functions as a risk marker of OPMD malignant transformation risk.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024626482, identifier: CRD42024626482).